Citizen Charter in Nepali Public Sector Organizations: Does it Really Work? - Anil Kumar Gupta; Gyan Laxmi Shrestha (Indonesian Association for Public Administration, 2021)
Citizen Charter is an instrument of citizen-centric governance that confirms quality in public service delivery by holding public sector organizations directly accountable, responsive, and transparent. In this regard, this study aimed to disclose the current picture of Citizen Charter in Nepali public sector organizations from service users’ perspectives. For this, the survey was conducted in key six public sector organizations of Lalitpur Metropolitan City by using the client exit interview method, with the help of a semi-structured interview schedule. The study result indicates that the use of the Citizen Charter is extensively low. Service users are not fully aware and well informed about it, and its values. Service users prefer to receive services by asking from duty holders, intermediates (agents), and previous service users than the Citizen Charter. Service users believe that the promises of the Citizen Charter and the behavior of duty holders are inconsistent. However, some service users are demanding services as per the Citizen Charter.